Kajian Terhadap Putusan Batal Demi Hukum Tanpa Perintah Penahanan (Studi Putusan Mahkamah Konstitusi No. 69/PUU-X/2012) - Rifai, Eddy (Mahkamah Konstitusi Republik Indonesia, 2013)
Thispaperexaminesthe decisionaboutthe null andvoidwithout anarrestwarrant (the decision of the Constitutional Court No. 69/PUU-X/2012). From the results of the discussion suggests that the Criminal Code does not provide an explanation of the term “null and void”. The term “null and void” in the sense of directing an action does not match the Criminal Procedure Code. Criminal Procedure Code provides limitatif limits on detention, both for conditions of detention, agency/law enforcement detain and duration of detention, where errors in detention may be submitted claim for compensation. Constitutional Court Decision No. 69/PUU-X/2012 dated 22 November 2012 stating that the court decision does not comply with Article 197 paragraph (1) Criminal Code specifically on the restraining order was not void is not appropriate, because the terms of the restraining order is necessary for the detention status of the accused, whether fixed detained or released or against the accused who were not arrested were ordered to be detained. Court decisions that do not comply with Article 197 paragraph (1) Criminal Code specifically about a restraining order is null and void. Against the decision of the void can be corrected by the court restraining order stating thereon.